Dinner in Camelot : the Night America's Greatest Scientists, Writers, and Scholars Partied at the Kennedy White House - Esposito, Joseph A. (University Press of New England : ForeEdge, 2018)
"I think this is the most extraordinary collection of talent, of human knowledge, that has ever been gathered together at the White House, with the possible exception of when Thomas Jefferson dined alone."--President John F. Kennedy, April 29, 1962